Rare Recurrent EWSR1-PLAGL1 Rearranged Intracranial Tumor With Biphasic Epithelioid Differentiation: One Case Report With Literature Review - Xing, Ai-yan; Yang, Wen-wei; Liu, Yu-lu; Sun, Nan-nan; Hao, Xiao-meng; Wang, Su-xia; Mu, Kun (Frontiers in Oncology, 2022)
EWSR1-rearranged tumors encompass a rare and heterogeneous group of entities with features of the central nervous system (CNS) mesenchymal and primary glial/neuronal tumors. EWSR1-PLAGL1 gene fusion is a particularly rare form of rearrangement. We presented a recurrent intracranial EWSR1-PLAGL1 rearranged tumor and reviewed the relevant literature. In this case, histopathology and immunohistochemistry (IHC) were evaluated for both the primary and relapsed tumors. Fluorescence in situ hybridization (FISH) and next-generation sequencing (NGS) were performed for the relapsed tumor. We compared the morphology, IHC results and molecular features with the previously reported EWSR1-PLAGL1 rearranged CNS tumors. Our case exhibited a unique feature with a variable biphasic pattern of epithelioid differentiation, which differed from the two reported groups. The primary and relapsed tumors both expressed cytokeratin of the focal area with epithelioid differentiation. The recurrent tumor showed an increased proliferation index (average Ki-67 index of 15%) compared with the primary tumor (average Ki-67 index of 5%). NGS showed that TERT promoter mutation was the only molecular change besides EWSR1-PLAGL1 fusion. Our study provides further insight into intracranial tumors with EWSR1-PLAGL1 fusion, representing a distinct CNS tumor with no-reported histological and immunohistochemical features. Future studies, particularly for the biphasic differentiation and the role of TERT promoter mutation were needed to clarify this unusual chromosomal rearrangement in the CNS tumor.